Clinical Experience and Management Strategy of Retroperitoneal Tumor With Venous Tumor Thrombus Involvement - Liu, Zhuo; Ge, Liyuan; Liu, Lei; Zhao, Xun; Chen, Kewei; Li, Yuxuan; Aili, Abudureyimujiang; Lu, Min; Pei, Xinlong; Han, Dengyang; Zhang, Shudong; Ma, Lulin (Frontiers in Oncology, 2022)
Background: To report the surgical management, complications, and outcomes for patients with retroperitoneal tumor and venous thrombus Methods: We retrospectively analyzed 19 cases of retroperitoneal tumor with venous tumor thrombus from August 2015 to March 2021. According to the characteristics of surgical techniques, a new tumor thrombus PUTH grading system was proposed. Results：There were 2 cases of PUTH-1a, 2 cases of PUTH-1b, 6 cases of PUTH-2, 6 cases of PUTH-3,3 cases of PUTH-4. All the operations were successfully performed in 19 patients. Among them, 5 cases (26.3%) were operated by completely laparoscopic approach and 13 cases (68.4%) were operated by open approach. One case (5.3%) was converted from laparoscopic approach to open approach. 5 cases experienced postoperative complications, the incidence was 26.3%. All the cases were followed-up for a median of 14 months. Cancer associated death were occurred in 3 cases. Distant metastases were occurred in 7 cases. Conclusions：In this study, we proposed a new tumor thrombus grading system based on the anatomical characteristics of ret-roperitoneal tumors with venous tumor thrombus. Retroperitoneal tumor resection and removal of venous tumor thrombus are safe and effective in the treatment of such diseases.